N-Continuous Functions in Bitopological space - عفيصه براءه (Latakia University Journal -Basic Sciences Series, 2023)
Let iscontinuous functions in bitopological space ,where,are two bitopological space. In this research ,I have studied some properties of continuous functions in bitopological space, from the most important is: 1- is continuous function if and only if isclosed set infor each closed set in. 2- everycontinuous function is continuous function, but the converse is not right in general. Moreover, I have defined a new concept in bitopological space called homeomorphism function , but the converse is not right in general.